Dressmaking (casual) intermediate - 3G Elearning (UAE 3G Elearning FZ LLC, 2016)
"Dressmaking (Casual) - Intermediate combines many different practical and visual skills with knowledge of specialized materials and techniques. This book will introduce the knowledge and skills for those studying and/or working in garment industry"--Provided by publisher.
Keywords: Dressmaking